Early Stimulation and Cognitive Resilience: Reorienting Early Childhood Pedagogy in Shaping A Superior Generation - Yuli Martuti; Eka Pariyani; Umi Istikhanah (Program Studi PGSD Universitas Madako Tolitoli, 2026)
The golden age is a critical phase in child development; however, in Indonesia, it is still challenged by developmental delays, limited educational facilities, and low parental awareness of early stimulation. This study aims to analyze the role of early stimulation and cognitive resilience in the pedagogical reorientation of early childhood education. A descriptive qualitative approach was employed through literature review, enriched by empirical insights from PAUD PKK Latifa Gisting. Data were obtained from primary and secondary sources, including reputable journal articles, academic books, and relevant scientific publications, using documentation techniques. Data analysis was conducted through content analysis involving data reduction, thematic categorization, and reflective synthesis. The findings indicate that developmental stimulation, play-based learning, and character strengthening significantly contribute to the formation of cognitive resilience. Cognitive resilience is conceptualized as a dynamic construct shaped by learning experiences, emotional regulation, and environmental support. The study highlights the importance of integrating six aspects of resilience collaboratively by teachers and parents within a holistic and safe learning environment. These findings imply the need for policy strengthening, enhancement of educator competence, and synergy among families and communities to foster an adaptive and resilient generation.